Regionalization, Performance Management and Software Technology - Simona BIRIESCU (Revista de Management Comparat International)
It is estimated that future economic development will lead to population growth in the coming years. To solve the complex problems of this growth, the logic of the historical evolution of the city recommends continuing its radial structure - focused. This is done if we talk about performance management in regionalization. Knowing that performance management is a way to achieve individual and organizational development, it is advisable to have a better understanding of performance management in a unified framework and context of business. Performance management is a systematic approach to human resources management in general, and performance evaluation in particular. Regionalization of a process that depends on people management, informatics and performance leads to “balanced socio-economic development of the regions, improving quality of life, responsible management of natural resources, environmental protection and rational use of the land. We must take into account the fact that the EU promotes and encourages regionalization by allowing direct access to funds at this level, but has no discretion and no pressure instruments in this regard, and Member States, most do not seek a deeper regionalization (the actual transfer decision-making power).